Incidence and Prevention of Cicatricial Scleral Show in the Subciliary Access in Patients With Orbital Fractures. Issue 6 (September 2019) - Fernandes Lopes Morais D'Autilio, Margarida; Bottini, Davide Johan; Basile, Emanuela; Lovero, Stefano; Sanese, Giuseppe; de Angelis, Barbara; Chaboki, Houtan; Cervelli, Valerio
Abstract : N/A: Orbital fractures can involve floor, lateral and medial wall. Surgical access depends on fracture's severity, ocular trauma and patient's age. Subciliary, subtarsal, infraorbital or transconjunctival approaches are the main access to the orbit. Surgical interventions in the eyelid may induce scar tissue formation and, consequently, the cicatricial scleral show. The authors present a study with the aim to evaluate the incidence of cicatricial scleral show in patients treated for orbital fractures with or without simultaneous Tarsal Sling Canthopexy in our Plastic Surgery Department. Methods: The authors evaluated 50 patients divided in 2 groups: Group 1, subciliary approach and reconstruction of orbital floor without simultaneous Canthopexy Tarsal Sling; Group 2: reconstruction of orbital floor through subciliary approach with simultaneous Canthopexy Tarsal Sling. Results: Patients, who underwent Canthopexy Tarsal Sling, did not have any scleral show. Instead patients, who did not undergo this prevention technique, had scleral show even if a minor entity. Discussion: Although there was no muscle or skin removed, in our procedure, but only cutaneous incision, scleral show can appear as a complication. Canthal ligament and tarsus' elasticity influence the incidence of post-surgical scleral show, which is more frequent in elderly patients. Therefore, the authors suggest to prevent it routinely with Tarsal Sling Canthopexy. Conclusion: Canthopexy Tarsal Sling is procedure that stretch tarsal structure and it may help to prevent scleral show.